1997
DOI: 10.1111/j.1540-8191.1997.tb00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoplasia of the Posterior Leaflet as a Rare Cause of Congenital Mitral Insufficiency

Abstract: A rare case of congenital mitral insufficiency characterized by the hypoplasia of the posterior leaflet is reported. At operation, the mitral valve was successfully repaired by a ring annuloplasty, which created a satisfactory surface of coaptation between the anterior leaflet and the bulky posterior muscular structure. The presence of this posterior muscular structure represents a developmental arrest at the stage of conversion from muscular chordae and leaflets to thin connective structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…They reported this congenital anomaly as a consequence of developmental arrest at the stage of chordae and leaflets conversion from muscular to thin connective structures. Muscular structure of the PML that has been reported in some pediatric cases will also accelerate the process of annular dilatation and development of mitral regurgitation …”
Section: Discussion and Review Of The Literaturementioning
confidence: 98%
“…They reported this congenital anomaly as a consequence of developmental arrest at the stage of chordae and leaflets conversion from muscular to thin connective structures. Muscular structure of the PML that has been reported in some pediatric cases will also accelerate the process of annular dilatation and development of mitral regurgitation …”
Section: Discussion and Review Of The Literaturementioning
confidence: 98%
“…The final atrioventricular valves are derived entirely from endocardial cushion tissue 8 . This hypothesis has been previously supported by the presence of myocytes in biopsy specimens of the valvular remnants 2 …”
Section: Commentmentioning
confidence: 67%
“…8 This hypothesis has been previously supported by the presence of myocytes in biopsy specimens of the valvular remnants. 2 Our patient has congenital hypoplasia of the right upper and middle lobes of the lungs in addition to valvular anomaly. In previous studies, connective tissue diseases and thoracic skeletal abnormalities have been found to be associated with congenital valvular anomalies.…”
mentioning
confidence: 80%
See 2 more Smart Citations